1995
DOI: 10.1074/jbc.270.10.5266
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipid-gated Ca2+ Release from Intracellular Stores of Endothelial Cells Is Mediated by a Novel Ca2+-permeable Channel

Abstract: Sphingolipid-gated Ca2+ signaling is mediated through Ca(2+)-permeable channels. In this report, we characterize the properties of the channel in a human endothelial cell line (EA.hy926). Ca2+ release from intracellular stores is not antagonized by nifedipine, omega conotoxin G-VIa, or heparin. To further characterize the molecular properties of the channel, we developed a novel assay to directly measure efflux of Ca2+ from intracellular stores of permeabilized Xenopus oocytes. Following size fractionation by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
30
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 28 publications
0
30
0
Order By: Relevance
“…It is not blocked by La3, a prototypical blocker of Ca> selective channels, nor is it blocked by heparin, nifedipine, w-conotoxin, or Ni2+, all selective blockers of specific classes of voltage-gated and ligand-gated intracellular and plasma membrane Ca>+ channels. We developed an assay to examine expression of sphingolipid-gated Ca2+ release from the intracellular stores of Xenopuls oocytes (6). With this, we demonstrated that the mRNA encoding the intracellular sphingolipid-gated Ca2+ release activity is 1.8 kb, much smaller than the 1 16-kb ryanodine receptor message (7), or the -9-kb message…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is not blocked by La3, a prototypical blocker of Ca> selective channels, nor is it blocked by heparin, nifedipine, w-conotoxin, or Ni2+, all selective blockers of specific classes of voltage-gated and ligand-gated intracellular and plasma membrane Ca>+ channels. We developed an assay to examine expression of sphingolipid-gated Ca2+ release from the intracellular stores of Xenopuls oocytes (6). With this, we demonstrated that the mRNA encoding the intracellular sphingolipid-gated Ca2+ release activity is 1.8 kb, much smaller than the 1 16-kb ryanodine receptor message (7), or the -9-kb message…”
mentioning
confidence: 99%
“…Until recently, the mechanism by which sphingolipids could release Ca2+ from intracellular stores was unknown. We have described the electrophysiological and biophysical properties of a sphingolipid-gated intracellular Ca'+-permeable channel (5,6). The sphingolipidgated Ca2+-permeable channel is unlike other known channels.…”
mentioning
confidence: 99%
“…An interesting observation made recently is that sphingosines regulate the gating of a novel type of calcium channel located in membranes of intracellular calcium stores in endothelial cells (11). Furthermore, sphingosines inhibit calcium entry through voltage-operated calcium channels (VOCCs) in cardiac cells (12), and capacitative calcium entry in Jurkat T cells (13).…”
mentioning
confidence: 99%
“…Because SCaMPER has been shown to be a calcium channel expressed by human basophilic leukemia cells and canine MDCK cells (4,5,14), localization of this channel to the junctional regions of cardiac cells suggested that it might have an important role in cardiac calcium control. Accordingly, we demonstrated that SPC, the well-recognized sphingolipid ligand for SCaMPER, elicits profound calcium release from the cardiac SR.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, sphingolipids have been shown to mediate a variety of cellular events such as proliferation, apoptosis, and calcium signaling (10). The diverse effects of sphingolipid mediators are in part explained by the finding that these signaling molecules have direct intracellular actions as well as acting on surface membrane receptors (4).…”
mentioning
confidence: 99%